2014
DOI: 10.1002/2013wr013909
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of impervious surfaces to urban evaporation

Abstract: Observational data and the Princeton urban canopy model, with its detailed representation of urban heterogeneity and hydrological processes, are combined to study evaporation and turbulent water vapor transport over urban areas. The analyses focus on periods before and after precipitation events, at two sites in the Northeastern United States. Our results indicate that while evaporation from concrete pavements, building rooftops, and asphalt surfaces is discontinuous and intermittent, overall these surfaces ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(70 citation statements)
references
References 67 publications
2
62
0
1
Order By: Relevance
“…Since our study area is in the urban setting, evaporation over impervious surfaces did not follow the evaporation characteristics that have been found in soil and vegetated areas. Ramamurthy and Bou-Zeid [17] suggested that substantial contribution from impervious surfaces to urban evaporation usually occurs in the first 48 hours after precipitation. Since the amount of precipitation was below 1mm within 48 hours prior to both image acquisition dates, the urban evaporation conditions of the two dates were assumed to be similar.…”
Section: Methodsmentioning
confidence: 99%
“…Since our study area is in the urban setting, evaporation over impervious surfaces did not follow the evaporation characteristics that have been found in soil and vegetated areas. Ramamurthy and Bou-Zeid [17] suggested that substantial contribution from impervious surfaces to urban evaporation usually occurs in the first 48 hours after precipitation. Since the amount of precipitation was below 1mm within 48 hours prior to both image acquisition dates, the urban evaporation conditions of the two dates were assumed to be similar.…”
Section: Methodsmentioning
confidence: 99%
“…of PFD will presumably be greater for regions with a larger proportion of impervious surfaces, as these surfaces have very low evaporation under dry conditions but can support very high evaporation rates when wet (Ramamurthy and Bou-Zeid, 2014;Ward et al, 2015). This is supported by Figure 7, which shows the annual difference in modelled evaporation and runoff for different resolutions of PFD for a range of surface cover fractions.…”
Section: Surface Covermentioning
confidence: 70%
“…E-mail: h.c.ward@reading.ac.uk et al, 2015). For example, Ramamurthy and Bou-Zeid (2014) showed that following precipitation events over a wet 10-day period, nearly 17% of the total latent heat flux was from impervious surfaces. Evidence of increased evaporation rates 12-18 h after rain has been observed in central London (Kotthaus and Grimmond, 2014) and in Toulouse (Wouters et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The contrast between patches of hot, dry impervious areas and cool, wet vegetation may be reduced by altogether wetter surfaces in 2012, which is thought to increase correlation between temperature and humidity (Lamaud and Irvine, 2006;Moene and Schüttemeyer, 2008;Ramamurthy and Bou-Zeid, 2014). On the other hand, Lüdi et al (2005) found lower r T q coincides with lower β.…”
Section: Temperature-humidity Correlationmentioning
confidence: 98%
“…EC data from open-path gas analysers cannot be used if the instrument windows are wet, such as during and after rainfall (Heusinkveld et al, 2008). Consequently, water vapour measurements from open-path systems significantly under-represent these times and may result in an appreciable underestimation of mean Q E (Ramamurthy and Bou-Zeid, 2014) and C 2 q . Mean values for C 2 T calculated using daytime data only when all quantities are available concurrently (i.e.…”
Section: Comparison Of Eddy Covariance and Scintillometry Techniquesmentioning
confidence: 99%